2022
DOI: 10.3389/fcell.2022.884467
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling in the Breast: From Development to Disease

Abstract: The Wnt cascade is a primordial developmental signaling pathway that plays a myriad of essential functions throughout development and adult homeostasis in virtually all animal species. Aberrant Wnt activity is implicated in embryonic and tissue morphogenesis defects, and several diseases, most notably cancer. The role of Wnt signaling in mammary gland development and breast cancer initiation, maintenance, and progression is far from being completely understood and is rather shrouded in controversy. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 168 publications
1
12
0
Order By: Relevance
“…Aberrant Wnt signaling plays a critical role in mammary gland development and breast tumorigenesis [ 22 , 23 ]. STAT3 signaling possesses multifaceted functions in the immune response in the breast tumor microenvironment and has downstream target genes that overlap with the Wnt signaling pathway [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aberrant Wnt signaling plays a critical role in mammary gland development and breast tumorigenesis [ 22 , 23 ]. STAT3 signaling possesses multifaceted functions in the immune response in the breast tumor microenvironment and has downstream target genes that overlap with the Wnt signaling pathway [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, evaluating prognosis and monitoring tumor response in real time during treatment continues to be an unmet clinical need in advanced BC ( Gupta et al, 2020 ). Wnt signaling is a very relevant pathway in BC whose molecular alterations have clinical implications to establish the prognosis of the disease ( Mukherjee et al, 2012 ) and has been associated to breast cancer therapy response ( Abreu de Oliveira et al, 2022 ). Therefore, it would be interesting to evaluate in future studies whether the hypermethylation of WNT1 could be useful for the selection of patients susceptible to systemic therapies (CDK inhibitors for example) in the BC metastatic setting.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports showed that during development components of the FGF, Wnt, Notch, BPM, and Hedgehog signaling orchestrate crucial cellular events including proliferation, migration, differentiation, epithelial-mesenchymal transition (EMT), morphogenesis and somite myogenesis patterning. When gene expression controlling these events is dysregulated, it leads to disease induction ( Hansson et al, 2004 ; Logan and Nusse, 2004 ; Ma et al, 2010 ; Teven et al, 2014 ; Xiao et al, 2017 ; Abreu de Oliveira et al, 2022 ; Alrefaei and Abu-Elmagd, 2022 ; Towler and Shore, 2022 ). Although our RT did not receive microRNA-related manuscripts, it is well-established that microRNAs play an important role in physiology and disease ( Sayed and Abdellatif, 2011 ; Bhaskaran and Mohan, 2014 ; Kalayinia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%